Reference guide : normative developments on the coordination of humanitarian assistance in the General Assembly and the Economic and Social Council since the adoption of General Assembly resolution 46/182 - United Nations. General Assembly; United Nations. Economic and Social Council; United Nations. Security Council; United Nations. Office for the Coordination of Humanitarian Affairs. Policy Development and Studies Branch (New York : United Nations, 2011)
"General Assembly resolution 46/182 provided the framework for emergency relief, ... broadly addressed how to strengthen the coordination of the humanitarian system." This updated guide is intended to provide a concise overview of the normative evolution of key policy decisions of the General Assembly and the Economic and Social Council on humanitarian affairs through resolutions since 1991. It should be used as a complement to Phase II, Reference guide: Normative decisions of key governing bodies ... --Preface
"20th anniversary of General Assembly resolution 46/182."
"November 2011".
Keywords: United Nations; Humanitarian assistance